Risk Factors for Sudden in-hospital Cardiac Death in Patients with ST-segment Elevation Acute Myocardial Infarction - Antonio Rafael Enamorado Anaya; Isolda María García Cañete; Marilín González Agüero; Gaoussou Goro (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Background: although advances in the treatment of acute myocardial infarction have led to a reduction in the risk of sudden death in the long term, it remains high in certain subgroups of patients. Objective: to identify the risk factors for sudden in-hospital cardiac death in patients with ST-segment elevation acute myocardial infarction. Methods: an analytical study of cases and controls was carried out in the Cardiology service of the Celia Sánchez Manduley Provincial Clinical Surgical Hospital in Manzanillo, Granma province from 2016 to 2019. 41 defined cases were studied. For each one 2 living graduates were randomly chosen. Variables dependent on the patient, examinations and treatment performed were studied. The absolute and relative frequency calculation was performed. The arithmetic mean with standard deviation was determined and compared using the Student's t test. The Chi-square test was used for qualitative variables. Risk factors were determined using a logistic regression model. Results: male sex prevailed (56 %) and the mean age was 73.3 years. As risk factors, the following were determined: a history of heart failure, presenting the Killip Kimball classification III-IV, as well as fasting first glycemic levels greater than 10 mmol / L and creatine phosphokinase greater than 180 IU. Conclusions: the most prevalent risk factors were: arterial hypertension, smoking, as well as peripheral arterial insufficiency, the presence of diabetes and obesity.